I need help finishing this proof. I've come to a point where I don't know how to continue. I need to prove that the following inequality is true for all positive integers $n$.

$$\sum_{i=1}^{n-1} (-1)^{i+1}i! \leq \frac{(2n)!}{2}$$

It's true for $P(1)$, now I consider the inequality to be my inductive hypothesis, I want to show that $\sum_{i=1}^{n} (-1)^{i+1}i! \leq \frac{(2n+2)!}{2}$ it's true for $(n+1)$. Taking my i.h.

$$\sum_{i=1}^{n-1} (-1)^{i+1}i! + (-1)^{n+1}n! \leq \frac{(2n)!}{2}+ (-1)^{n+1}n!$$

I should consider even and odd n's differently, when I consider an odd $n$

$$\sum_{i=1}^{n-1} (-1)^{i+1}i! + n! \leq \frac{(2n)!}{2}+ n!$$

So I should check that $\frac{2n!}{2}+ n! \leq \frac{(2n+2)!}{2}$ right? This takes me to:

$$\frac{(2n)!}{2}+ \frac{2(n!)}{2} \leq \frac{(2n+2)!}{2}$$

$$(2n)!+ 2(n!) \leq (2n+2)!$$

Am I on the right path here? How can I prove this inequality? Should I make an auxiliar proof by induction or is it self-evident as it is?


  • 1
    $\begingroup$ Hint: $(2n)!+ 2(n!) \leq (2n)!+ 2(\color{red}{2}n)! \leq 3(2n)!$ $\endgroup$ – Steve Kass May 10 '16 at 18:14

You’re doing fine, though you don’t need to treat even and odd $n$ separately: clearly $\frac{(2n)!}2-n!<\frac{(2n)!}2+n!$, so it’s sufficient to show that you always have


or, equivalently, that


HINT: Show that $2n!\le(2n)!$, so that $(2n)!+2n!\le 2(2n)!$, and then compare this with $(2n+2)!$.


That inequality is quite weak. We have to bound: $$ \sum_{i=1}^{n-1} (-1)^{i+1} i! = (-1)^n \sum_{j=1}^{n-1}(-1)^{j+1}(n-j)! $$ but the terms of the last sum are decreasing in absolute value, hence $\sum_{j=1}^{n-1}(-1)^{j+1}(n-j)!$ is between $(n-1)!=(n-1)\cdot(n-2)!$ and $(n-1)!-(n-2)! = (n-2)\cdot (n-2)!$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.